1993
DOI: 10.1002/ajmg.1320460604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular analyses of deletion 3p25‐pter syndrome

Abstract: Hemizygous deletion of 3p25-pter is associated with a phenotype of profound growth failure, microcephaly, characteristic facial changes, and mental retardation. Since the severity may be quite variable, we have studied 3 cases of del 3p25-pter to define the clinical manifestations and the critical chromosome region for phenotypic expression. The patient we now report died at age 6 months and provided an opportunity for a detailed necropsy analysis for only the second time in a del(3p) patient. He had marked hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…This young woman shows hypotonia and severe MR, features characteristic for 3p Ϫ patients, but not microcephaly, growth failure, heart and renal defects, and the 3p Ϫ typical facial abnormalities (13,14). The translocation breakpoint on chromosome X is located outside of any coding region.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This young woman shows hypotonia and severe MR, features characteristic for 3p Ϫ patients, but not microcephaly, growth failure, heart and renal defects, and the 3p Ϫ typical facial abnormalities (13,14). The translocation breakpoint on chromosome X is located outside of any coding region.…”
mentioning
confidence: 89%
“…Recent studies (10,12,14) indicated that patients carrying terminal deletions of chromosome 3p are associated with MR and further multiple recurring symptoms depending on the size of their deletion. The deletion size is variable but generally encompass several megabases of DNA, as shown by microsatellite analyses.…”
Section: Screening Of 3pmentioning
confidence: 99%
“…The 3p − syndrome is characterized by MR associated with microcephaly, hypotonia, growth failure, heart and renal defects, and facial abnormalities (Mowrey et al 1993). A female patient exhibiting severe MR and hypotonia, but none of the other classical 3p − symptoms, was found to possess a balanced translocation, with one of the breakpoints mapping within the 3p − deleted region.…”
Section: Autosomal Syndromic Mrmentioning
confidence: 99%
“…Subsequent studies also found MEGAP deleted in 3p − syndrome patients that present MR. These patients exhibit in addition to MR, microcephaly, growth failure, heart and renal defects, hypotonia and facial abnormalities [59].…”
Section: Megapmentioning
confidence: 99%